Strain effect on extracellular laccase activities from Botrytis cinerea. (12th December 2017) - Quijada‐Morin, N.; Garcia, F.; Lambert, K.; Walker, A.‐S.; Tiers, L.; Viaud, M.; Sauvage, F.‐X.; Hirtz, C.; Saucier, C.
Abstract: Background and Aims: Laccase enzymes produced by Botrytis cinerea are involved in the oxidation of phenolic substances during the development of grey mould, which causes significant economic losses. The aim of this work was to study the structural and activity characteristics of the laccase enzymes secreted by three B. cinerea strains that are involved in the development of grey mould. Methods and Results: Laccase enzymes obtained from three B. cinerea strains [one reference strain (B05.10) and two strains obtained from two French vineyards (VA612 and RM344)] were characterised. Analysis by LC‐QTOF‐MS revealed that the three strains contained a mixture of Laccase‐2‐BcLCC2 and Laccase‐3‐BcLCC7. The structural characteristics of the laccases from the three strains, such as molecular weight and glycosylation degree, were identical. Nevertheless, their catalytic activities were significantly different. Conclusions: Differences in catalytic activities could be due either to possible differences in the relative amount of Laccase‐2‐BcLCC2 and Laccase‐3‐BcLCC7 produced by each strain or to differences in the glycosidic fraction of the enzymes. Significance of the Study: The severity of the infection caused by B. cinerea may be not only related to the infection level but also to the strain involved.